Determination of Principal Components for Characterizing the Drying of Sea Cucumbers (Stichopus japonicus Selenka) Using Far Infrared Radiation Drying and Hot Air Drying. Issue 10 (26th November 2017) - Moon, Ji Hoon; Chung, Dong Hwa; Pan, Cheol-Ho; Yoon, Won Byong
ABSTRACT: Principal component analysis (PCA) and multiple linear regression (MLR) were conducted to characterize the drying of sea cucumber (SC). Far infrared radiation drying (FIRD) and hot air drying (AD) were used to dehydrate SC. Thirteen variables—including the morphological, color, and textural properties of dried SC—were selected for statistical analysis. The analysis of these 13 variables yielded three principal components showing significant correlations. PCA showed that the first three components represented 86.2% of the total variation. The first principal component was primarily related to the morphological properties of SC. The principal components determined by the PCA were more strongly influenced by the morphological variables than by the drying method. Of the morphological variables, the weight of SC had the strongest influence on the drying time and rehydration ratio of FIRD and AD.